Tatalaksana Kejang Demam pada Anak Terkini - Setyo Handryastuti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
A febrile seizure is a seizure associated with an increase of body temperature of more than 38°C. This condition is not caused by the central nervous system (CNS) infection and electrolyte or metabolic imbalance. A febrile seizure can affect children from the age of 6 months to 6 years. A febrile seizure is the common cause of seizure in children with benign clinical course dan good prognosis which will disappear at six years old. The diagnosis is achieved based on clinical manifestation, and the clinician should exclude CNS infection, especially in complex febrile seizures. Based on the literature, the indication of supporting examination and therapy has changed significantly. Laboratory examination, electroencephalography, and imaging only indicated if the patient’s condition was in line with the guideline. Management of the febrile seizure consists of symptomatic and prophylaxis therapy. The recommendation of the febrile seizure treatment includes management during the seizure, intermittent prophylaxis therapy, and long-time maintenance therapy. The recommendation of the prophylaxis therapy was formed based on Indonesia’s condition. A febrile seizure is often the cause of a patient’s over-anxiety. Therefore, education about the good prognosis, clinical course, risk, and benefit of prophylaxis therapy is needed. General practitioners, pediatricians, and neurologic pediatricians are expected to implement the recommendation to minimalize the over-use of supporting examination and treatment.